UNLOCKING THE POTENTIAL OF PROJECT-BASED LEARNING: ELEVATING WRITING SKILLS IN ISLAMIC SCHOOL JUNIOR HIGH STUDENTS - Romsi, Abdur; Sulistyaningsih, Sulistyaningsih (Jurnal Visi Ilmu Pendidikan, 2024)
Project-based learning (PjBL), an innovative teaching approach that emphasizes active, student-centered learning through real-world projects, serves as a cornerstone for educational advancement. However, in the specific context of Islamic schools setting, there exists a recognized need for the improvement of writing skills among first-grade students. This Classroom Action Research (CAR) study, spanning two cycles with a cohort of 15 participants at Mts. Insan Madani, Situbondo, is dedicated to achieving significant advancements in writing skill proficiency through the implementation of PjBL. Findings from the study indicate marked enhancements in creativity, engagement, and collaborative abilities. Concurrently, certain challenges surfaced, particularly in the realms of time management and the necessity for more structured guidance during the initial stages of PjBL implementation. The implications of this research underscore the efficacy of PjBL in enhancing writing skills within an Islamic school setting, emphasizing the potential for the integration of PjBL as an educational approach to nurture essential writing skills. Nevertheless, it is crucial to acknowledge the importance of providing additional support in specific areas. Recommendations for future research encompass expanding the study to different grade levels and incorporating a more extensive participant pool to further validate the findings, thereby offering a comprehensive understanding of the broader impacts of PjBL on writing skill development within Islamic schools.